Evaluating High School Students' Views on Online Learning with Meeting Apps during COVID-19 - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Jurnal Pendidikan Jarak Jauh, 2023)
This descriptive qualitative research aims to explore students' experiences in online learning via meeting applications. The purposive sampling method was used to select 11 members of the "Ryca Study Group" as respondents. The interview results show that online learning through meeting applications has become the new norm during the Covid-19 pandemic. The majority of students feel able to understand some subjects well, but there are also technical challenges and a lack of direct interaction with teachers and classmates. Some students are happy with the flexibility of time and accessibility of online learning, while others feel less motivated and experience boredom. In improving online learning, students suggested more interesting material, use of on-cam features for better interaction, and more active teacher involvement. By combining these suggestions, schools can continue to improve the quality of online learning and provide a better learning experience for students.